(untitled) (Global Journal of Human-Social Science, 2016)
The failure of the state to contain the proliferation of foreign extremist groups and their links with domestic religious groups exacerbates the incidence of extremism and violence in the country It has been noted that the costs of crime are tangible and intangible economic or social direct or indirect physical or psychological individual or community In this essay the effects of insurgency are discussed under four headings namely national security socio-economic impact collapse of infrastructure humanitarian crisis and diplomatic relations